Enhancing the catalytic activity of hydronium ions through constrained environments - Liu, Yuanshuai; Vjunov, Aleksei; Shi, Hui; Eckstein, Sebastian; Camaioni, Donald M.; Mei, Donghai; Baráth, Eszter; Lercher, Johannes A. (Nature communications, 2017)
The dehydration of alcohols is involved in many organic conversions but has to overcome high free-energy barriers in water. Here we demonstrate that hydronium ions confined in the nanopores of zeolite HBEA catalyse aqueous phase dehydration of cyclohexanol at a rate significantly higher than hydronium ions in water. This rate enhancement is not related to a shift in mechanism; for both cases, the dehydration of cyclohexanol occurs via an E1 mechanism with the cleavage of C β –H bond being rate determining. The higher activity of hydronium ions in zeolites is caused by the enhanced association between the hydronium ion and the alcohol, as well as a higher intrinsic rate constant in the constrained environments compared with water. The higher rate constant is caused by a greater entropy of activation rather than a lower enthalpy of activation. These insights should allow us to understand and predict similar processes in confined spaces. Alcohol dehydration can be challenging in aqueous phase. Here the authors show that hydronium ions confined with zeolite pores catalyse alcohol dehydration at a significantly increased rate relative to aqueous phase hydronium ions, driven by an increased association between the ion and alcohol and a greater entropy of activation.